Conversion of the Belis Benjer Tradition into Financial Statements as a Form of Economic and Cultural Value in the Customary Law of Lusitada Village - Jaeng, Wihelmina Maryetha Yulia; Tunya, Maria Grasella; Meka, Kornelius Yoseph Paga (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2025)
This study analyses the belis benjer tradition in Lusitada Village, Sikka Regency, as a form of economic and cultural value within customary law. The belis tradition, which involves the exchange of goods and animals between men and women in customary marriages, is transformed into financial statements to understand the economic aspects of this tradition. The purpose of the study is to convert the Belis Benjer tradition into a financial statement format that can provide the people of Lusitada Village with an understanding of the values and culture inherent in customary law, while also preserving the local culture. The method employed is a Mixed-Methods Approach with a sequential exploratory design, comprising four stages: collection and analysis of qualitative data, identification of features for testing, quantitative testing of the designed features, and interpretation of the test results. The research results indicate that the conversion of the belis benjer tradition into financial statements shows higher profits for women than for men; however, culturally, belis serves as a recognition of women's dignity and reinforcement of family relationships. This research is expected to provide useful information for the preservation of the belis tradition in Lusitada Village as well as for customary management policies that are more in line with local customary law.